Dampak Buruk dari Media Sosial terhadap Status Keislaman Seorang Muslim - Abdul Khalim, Yasir (Pascasarjana UIN Raden Mas Said Surakarta, 2022)
It is undeniable that the development of technology that occurs can be felt, especially in the rapid spread of information with the existence of social media. The purpose of this research is to analyze the impact caused by the dissemination of information circulating on social media that endangers the Islamic status of a Muslim and provide solutions that can be done to prevent harm to the Muslim. This research uses descriptive qualitative method with data collection done by literature study. The result of this research is that social media users tend to imitate what is received from social media and one of the things circulating on social media is an Islamic invalidation which includes making fun of Islamic teachings and shirk. The conclusion that can be drawn is that a filter is needed for a Muslim in using social media in order to avoid things that endanger his Islamic status by studying religious knowledge, one of which is correct aqidah.